BIG DATA AND AI FOR IMPROVING MARKETING DECISION-MAKING IN DISTRIBUTION COMPANIES - Jamoliddinov Fakhriyor Shodiyor ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article examines the transformative role of Big Data and Artificial Intelligence (AI) in enhancing marketing decision-making within distribution companies. It explains how AI enables a strategic shift from descriptive reporting toward predictive insights and prescriptive, value-creating actions. Key applications include trade promotion optimization, dynamic pricing strategies, and highly personalized retailer engagement. The article also presents a maturity model for effective adoption and emphasizes that leveraging AI represents not only a technological enhancement but also a strategic opportunity to strengthen marketing ROI and achieve long-term, sustainable competitive advantage in an increasingly data-driven marketplace.